Extrahepatic Manifestations of Nonalcoholic Fatty Liver Disease - Li, Andrew A. (Gut Liver, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and encompasses a spectrum of pathology from simple steatosis to inflammation and significant fibrosis that leads to cirrhosis. NAFLD and its comorbid conditions extend well beyond the liver. It is a multisystemic clinical disease entity with extrahepatic manifestations such as cardiovascular disease, type 2 diabetes, chronic kidney disease, hypothyroidism, polycystic ovarian syndrome, and psoriasis. Indeed, the most common causes of mortality in subjects with NAFLD are cardiovascular disease, followed by malignancies and then liver-related complications as a distant third. This review focuses on several of the key extrahepatic manifestations of NAFLD and areas for future investigation. Clinicians should learn to screen and initiate treatment for these extrahepatic manifestations in a prompt and timely fashion before they progress to end-organ damage.